Ball-bearing dynamics modelling by a bond graph approach. (2nd January 2022) - Ovy, Enaiyat Ghani; Sun, Qiao
ABSTRACT: This research is dedicated to developing an analytical physics-based model of rolling element bearing, especially focused on ball bearing. The mathematical model is built on the dynamics of planner rigid bodies having body fixed frames that consider inner ring, eight balls and outer ring. The distinguishing feature of the model is the capability to accurately locate all contact points between inner ring-balls, and balls-outer ring during its entire operation. This is possible as we chose bond graph as the modelling tool that considers precise bearing geometry and magnificently connects each point of the multi-body system by calculating relative velocities at contact points of the corresponding contacting pairs. The model also shows the effect of load zone on bearing parts, where contact deformation is calculated using Hertz contact theory. The condition of contact is applied while considering the clearance as well. The effects of faults on bearing are investigated in the end. With the help of bond graph, a modular program has been developed, which efficiently considers the dynamics of all the bearing components simultaneously. The model is validated by conducting a virtual experiment in SOLIDWORKS and comparing results with a literature as well.